2008
DOI: 10.1007/s00406-008-0839-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with choice of psychotropic drugs used for intentional drug overdose

Abstract: Prescription of the psychotropic drugs plays an important role in the choice of the drugs ingested for the IDO. It might make potentially "dangerous" drugs available for the patient. Physicians have always to balance the benefit of the treatment against the risk of drug overdose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 28 publications
2
27
0
Order By: Relevance
“…Previous studies have highlighted the importance of considering risk of IDO among patients prescribed minor tranquillisers 7 11 13. A previous Irish study found that having a prescription for a minor tranquilliser increased the risk of using a psychotropic drug in an IDO, independent of any other studied factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have highlighted the importance of considering risk of IDO among patients prescribed minor tranquillisers 7 11 13. A previous Irish study found that having a prescription for a minor tranquilliser increased the risk of using a psychotropic drug in an IDO, independent of any other studied factor.…”
Section: Discussionmentioning
confidence: 99%
“…Analgesics such as paracetamol are also common, particularly in England 12. It has been shown that the vast majority of IDO patients take their own medication whether prescribed or available over the counter 11 13 14. The prevalence of drugs taken in IDOs has been shown to reflect their prescription and availability in the population 6 15…”
Section: Introductionmentioning
confidence: 99%
“…Intentional drug overdose (IDO) is the most common form of hospital-treated deliberate self-harm [3,4]. In general, psychotropic drugs, such as minor and major tranquilizers, selective serotonin reuptake inhibitors (SSRIs) and barbiturates are over-represented in IDOs [5][6][7], accounting for up to 80% of IDOs involving prescription drugs [8]. In Ireland, approximately 68% of all hospital-treated episodes of deliberate self-harm involve an IDO [3], and, of these, minor tranquilizers (benzodiazepines) are present in approximately 43% of cases [9].…”
mentioning
confidence: 99%
“…Few studies, particularly in recent years, have focused on the source of medications taken in IDO acts. It has been consistently indicated that overdose patients primarily take their own medication in IDOs [5,10,11]. In addition, individuals who engage in IDOs are more likely to be depressed and to have previously engaged in selfharm compared with other self-harm patients who do not engage in IDOs [1,10,12].…”
mentioning
confidence: 99%
“…1 This reflects the facts that depression is the most frequent psychiatric disorder in people dying by suicide, 118 the method used for suicidal acts is often determined by availability 11 and self-poisoning in depressed individuals often involves antidepressants prescribed for them. 119 Relative toxicity is an important factor likely to determine the outcome of an antidepressant overdose. Studies using different approaches have shown wide variation in the relative toxicity of antidepressants, 120,121 with the older TCAs generally being more toxic than the newer SSRIs.…”
Section: Introductionmentioning
confidence: 99%